Reporting Violence in the Poetry of James Fenton: A Journalistic Account of the Confrontation (المجلة الدولية للعلوم التربوية والآداب, 2025)
The present article seeks to shed light on James Fenton's remarkable ability to report on ongoing events through poetry, which enables him to be characterized as a poet-reporter. Fenton integrates journalistic principles in his examination of political events, thereby contributing significantly to the documentation of modern history. As such, Fenton can aptly be regarded as a history reporter. This paper will center on the notion of journalistic historiography, specifically through the lens of Fenton's work in the contexts of two pivotal geopolitical locations: South Asia, and The Middle East. In the course of this study, particular attention will be devoted to the cultural features that have shaped the political circumstances of both locations. In South Asia, the poet highlights the struggle for independence and the visible decline attributed to colonial influence and related recurring violence. Concerning The Middle East, Fenton deals with the recycling of violence as he scrutinizes the cultural and political tensions in the region.